«Vivere da soldato senza essere tale». Gli scritti di guerra di Thomas Mann (Studia theodisca, 2013)
This essay examines the semantic area linked to military activity and in particular the conditions of the soldier in the essays written by Thomas Mann during the First World War. These reconstructions of a historical theme intermix with contributions about current public affairs, and have as their object the events linked to Germany’s entering the war and the general favour with which this was received. Moreover, warlike metaphors tend to slip comfortably into the profound core of Mann’s writing, since they lend themselves rather effectively to descriptions of the artist’s actual aptitudes and duties.